The Effect of Moderate Dietary Protein and Phosphate Restriction on Calcium‐Phosphate Homeostasis in Healthy Older Cats. (16th August 2016) - Geddes, R.F.; Biourge, V.; Chang, Y.; Syme, H.M.; Elliott, J.
Abstract : Background: Dietary phosphate and protein restriction decreases plasma PTH and FGF‐23 concentrations and improves survival time in azotemic cats, but has not been examined in cats that are not azotemic. Hypothesis: Feeding a moderately protein‐ and phosphate‐restricted diet decreases PTH and FGF‐23 in healthy older cats and thereby slows progression to azotemic CKD. Animals: A total of 54 healthy, client‐owned cats (≥ 9 years). Methods: Prospective double‐blinded randomized placebo‐controlled trial. Cats were assigned to test diet (protein 76 g/Mcal and phosphate 1.6 g/Mcal) or control diet (protein 86 g/Mcal and phosphate 2.6 g/Mcal) and monitored for 18 months. Changes in variables over time and effect of diet were assessed by linear mixed models. Results: A total of 26 cats ate test diet and 28 cats ate control diet. There was a significant effect of diet on urinary fractional excretion of phosphate ( P = 0.045), plasma PTH ( P = 0.005), and ionized calcium concentrations ( P = 0.018), but not plasma phosphate, FGF‐23, or creatinine concentrations. Plasma PTH concentrations did not significantly change in cats fed the test diet ( P = 0.62) but increased over time in cats fed the control diet ( P = 0.001). There was no significant treatment effect of the test diet on development of azotemic CKD (3 of 26 (12%) test versus 3 of 28 (11%) control, odds ratio 1.09 (95% CI 0.13–8.94), P = 0.92). Conclusions and Clinical Importance: Feeding a moderately protein‐ and phosphate‐restricted diet has effects on calcium‐phosphate homeostasis in healthy older cats and is well tolerated. This might have an impact on renal function and could be useful in early chronic kidney disease.